Early profile of glycaemia in very low birth weight infants - Szymońska, Izabela (2022)
In the study, a continuous glucose monitoring system was used to measure interstitial glucose levels in the group of very low birth weight (VLBW) infants. It was observed that hyperglycemia (glucose > 150 mg%) in VLBW infants is a common symptom and glucose levels >180 mg% were observed in more than a 1/3 of patients. VLBW infants with moderate/severe hyperglycemia received significantly lower intravenous glucose administration comparing to other groups. Lower gestational age and more severe clinical status were defined as a risk factors of hyperglycemia. No statistical differences regarding short and long-term consequences of prematurity between groups of hyperglycemia were noted. Lower gestational age was shown as risk factor of increased glycemic variability. Additionally, higher glucose variability and longer oxygenation exposure in VLBW infants are independent factors of developing a treatment requiring retinopathy of prematurity. A continuous glucose monitoring system was shown to be safe to use, with no side effects reported.
Keywords: prematurity; continuous glucose monitoring; hyperglycemia; glycemic variability; retinopathy of prematurity